Innovation‐adjusted economic complexity and growth: Do patent flows reveal enhanced economic capabilities?. Issue 1 (12th August 2021) - Lybbert, Travis J.; Xu, Mingzhi
Abstract: Understanding economic growth has been a primary pursuit for generations of economists. Hidalgo and Hausmann (2009) ( Proceedings of the National Academy of Sciences, 106, 10570–10575) charted new territory in this pursuit by using bipartite international trade networks to characterize the economic complexity of a country based on the capabilities implied by the products it exports. The resulting Economic Complexity Index (ECI) correlates strongly with income levels and predicts subsequent economic growth with some statistical precision. We propose an innovation‐adjusted ECI (i‐ECI) that uses a high‐resolution patent–trade concordance to construct trade networks weighted by domestic and international patent application flows. The i‐ECI thus reflects firms' decisions about where to seek patent protection on industry‐specific inventions, allows for heterogeneity in the relative importance of patenting across industries, and implicitly captures firms' perceived innovation potential in the recipient countries. Although the i‐ECI is highly correlated with the ECI (correlation coefficient greater than 92%), it is a stronger and more statistically precise predictor of economic growth than the unadjusted ECI.